PROFESIONAL GURU DALAM MENGHADAPI TANTANGAN PERKEMBANGAN TEKNOLOGI PENDIDIKAN - Muhammad Aspi; Syahrani (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
Professional teachers are the determining factor in the quality education process. Teachers in the current era of information and communication technology are not just teaching (transfer of knowledge) but must be learning managers, because education is a gateway to a better life by fighting for the smallest things to the biggest things that would normally be passed by every student. man. Education is required to be more advanced and easily accessible to all people. One of them, the creation of the "Industrial Revolution 4.0" in other words a digital-based era. One of the challenges of industry 4.0, namely in the world of education is the learning innovation carried out by Human Resources, in this case teachers by utilizing information technology facilities that are growing rapidly in this era. industrial revolution 4.0 so that it can play a role in improving the quality of learning. The challenge of education in this era is how to prepare teachers for the use of current technology and maximize the abilities of teachers in using the latest technological equipment. Therefore, Indonesia must immediately prepare professional educators, namely educators who are able to use e-learning, because the ability of educators to use technology is one solution to prepare a competent millennial generation.